Measuring Customer Service Quality in a South African Industrial Automation Company - Sali-Ameen, Mohammed (My University, 2011)
The study will be demarcated as follows. Chapter One has provided a background of some of the issues facing Honeywell Automation South Africa and some of the industry challenges. Pressure from competitors in the South African market is also discussed in this chapter. Chapter Two will review literature on the work of several authors on the generic determinant of service quality. A comparison of the factors identified reveals common elements. Some criticism is levelled against SERVQUAL, and the alternative INDSERV model is introduced. Chapter Three outlines the research design and methods for conducting this study. The data analysis techniques are explained and consideration given to the limitation/delimitation of this study, as well as issues relating to confidentiality, validity and reliability. Chapter Four and Five present the response data. The results of the study are integrated with the objective of this research, literature review and management models presented in the previous chapters. Chapter Six Conclusions have been drawn from the survey results and recommendations made for improving service quality at Honeywell Automation South Africa. A theoretical framework has been developed within the scope of this study to assist the company in improving customer service levels in order to gain competitive advantage
MBA thesis - WBS
Keywords: Customer service